Knowledge management : - Wallace, Danny P (Libraries Unlimited, 2007)
The strength of this book lies in the author's ability to pull together diverse philosophies and multiple theories as they relate to this "new" field called knowledge management. Wallace includes a fair representation of philosophies and highlights the contributions of each, using a writing style that is as simplified as advanced academic-level material permits. Collapsed biographies of philosophers are presented throughout the chapters, permitting readers insight into events that may have influenced their lives and thinking....This work recommends itself to library and information science faculty, students, and practitioners, and is considered required reading for courses in knowledge management. It is also useful for people in the computer sciences and human-computer interaction fields. Recommended. Upper-division undergraduates through professionals